Occasions of state
1 online resource.
Keywords: This sixth volume in the European Festival Studies series stems from a joint conference (Venice, 2013) between the Society for European Festivals Research and the European Science Foundation's PALATIUM project. Drawing on up-to-date scholarship, a Europe-wide group of early-career and experienced academics provides a unique account of spectacular occasions of state which influenced the political, social and cultural lives of contemporary societies. International pan-European turbulence associated with post-Reformation religious conflict supplies the context within which the book explores how the period's rulers and aelite families competed for power - in a forecast of today's divided world.